Takotsubo cardiomyopathy following blunt trauma: Early recognition and diagnosis - Sawyer Cimaroli; Yesha Maniar; James Ciancarelli; Adam Stright; D'Andrea Joseph (Trauma Case Reports, 2023)
Background: Takotsubo Cardiomyopathy (TTC) is characterized by reversible left ventricular apical ballooning in the absence of angiographically significant coronary artery disease. While TTC is usually preceded by an emotionally stressful event, physical trauma has been documented as a precipitating incident as well. Case summary: An 82-year-old female with no past medical history, presented to the emergency department following a motor vehicle collision. Trauma workup was significant for an ulnar fracture, elevated cardiac enzymes, and ST-segment changes. Bedside echocardiogram revealed apical ballooning. She underwent cardiac catheterization, which failed to demonstrate significant coronary artery disease. The patient developed cardiogenic shock and required temporary vasopressor support after failing a trial of intra-aortic balloon pump. Conclusion: Takotsubo Cardiomyopathy is a rare complication of trauma, which presents with signs and symptoms similar to acute coronary syndrome (ACS) but without evidence of obstructive coronary artery disease. Following trauma, signs of ACS in elderly women should raise provider's suspicion for TTC and prompting bedside echocardiography, which can assist with early diagnosis.